Serum sulfatide level is associated with severe systemic vasculitis with kidney involvement - Aomura, Daiki; Harada, Makoto; Nakajima, Takero; Nimura, Takayuki; Yamaka, Kosuke; Yamada, Yosuke; Hashimoto, Koji; Tanaka, Naoki; Kamijo, Yuji (Frontiers in Immunology, 2023)
Sulfatides are a type of sulfated glycosphingolipid that are secreted with lipoproteins into the serum. These molecules are involved in the inflammatory pathway of vessels in addition to coagulation and platelet aggregation. Previous studies have proposed that sulfatides play a pivotal role in regulating inflammation-related disorders. Systemic vasculitis (SV) diseases are generally caused by autoimmune diseases and often involve kidney vasculitis, which may lead to rapidly progressive kidney dysfunction and end-stage kidney disease. Our earlier pilot study revealed that the level of serum sulfatides (SS) was significantly decreased in patients with anti-neutrophil cytoplasmic antibody-associated vasculitis (AAV), a representative disease causing SV with kidney involvement (SVKI), especially in patients exhibiting active crescentic findings on kidney biopsy. To further explore the clinical significance of an association between SS and SVKI, we analyzed and compared the SS level of patients with various SVKI diseases in this retrospective cohort study. Among patients admitted to our hospital between 2008 and 2021, we ultimately enrolled 26 patients with IgA vasculitis (IgAV), 62 patients with AAV, and 10 patients with anti-glomerular basement membrane disease (GBM) as examples of SVKI diseases, as well as 50 patients with IgA nephropathy (IgAN) and 23 donors for living kidney transplantation as controls. The mean±standard deviation SS level in the donor, IgAN, IgAV, AAV, and GBM groups was 8.26±1.72, 8.01±2.21, 6.01±1.73, 5.37±1.97, and 2.73±0.99 nmol/mL, respectively. Analysis of patients in the SVKI diseases group showed that those with the crescentic class kidney biopsy finding exhibited significantly lower SS level than did those with other class biopsy features. Additionally, SS level had a higher detection ability for SVKI patients with crescentic class kidney biopsy findings (area under the receiver operating characteristic curve 0.90, 95% confidence interval 0.82 to 0.99) than did several other predictor candidates. Our results indicate that SS level is decreased in more severe SVKI diseases and may be associated with active glomerular lesions in SVKI kidney biopsy samples.